MEMPERKUAT KEWENANGAN PENGAWASAN KOMISI YUDISIAL MELALUI POLITIK HUKUM KEKUASAAN KEHAKIMAN - Iwan Sandi Pangarso (Universitas Muhammadiyah Gresik, 2019)
The authority of the Judicial Commission as an external supervisory body designed in the 1945 Constitution does not provide a constitutional basis that is ideal enough to play a role in the performance and behavior of judges. This was strengthened after the issuance of the Constitutional Court Decision No. 005 / PUU-VI / 2006 which states that it is unconstitutional and does not have the legal force to bind norms concerning supervision of constitutional judges because they are considered to cause legal uncertainty (rechtsonzekerheid). Based on these problems, this paper is intended to examine aspects of the authority that the KY has in a functional-constitutional manner. The authority of the Judicial Commission needs to be constitutionally strengthened through constitutional amendments so as not to be easily swayed by other legal products under it. In addition to the continued constitution amendment, it is necessary to provide executive authority to the KY through improving the law so that in exercising its authority effectively. This is intended so that the Judicial Commission can exercise its authority independently as long as it is based on constitutional law and has strong and binding legal force.